Genetic associations with longevity in a Calabrian cohort: an exploratory genome-wide study - Livia Beccacece; Paolina Crocco; Benedetta Torbidoni-Baldassari; Stefano Pallotti; Jie Huang; Michaël E. Belloy; Annibale A. Puca; Harold T. Bae; Paola Sebastiani; Giuseppe Passarino; Giuseppina Rose; Serena Dato; et al. (GeroScience, 2026)

Analysis of regulating ecosystem services at the mediterranean nature reserve of Castelporziano (Rome, Italy) in response to changing environmental conditions - G. Scarascia-Mugnozza; F. Manes; A. Sebastiani; S. Fares (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)
The Castelporziano Presidential Estate, a State Nature Reserve of roughly 6,000 hectares covered by natural forests, with over 30 years of field data collection is a precious data hub that might contribute to better understand the effects of Climate Change abiotic and biotic-related stress on natural vegetation and, eventually, to their ecosystem services provision. This research presents on-going studies on plant-environment interactions conducted within the Estate, with a focus on ecosystem carbon fluxes, pollution (ozone and particulate matter), drought and heat stress, and biotic infections that have occurred over time. The present study concentrates over the period from 2013 to 2024. In the first part, we present a series of continuous measurements on a semi-hourly basis, which was undertaken to build up a time series capable of interpreting the effect of the control factors (climate, ecological processes, water availability) on the eco-physiological parameters of the holm oak forest. Ten years of high-frequency measurements allowed us to estimate the possible effect of climate and water availability on carbon assimilation. The holm oak forest of Castelporziano showed high rates of carbon assimilation each year with minimal changes in response to drought and high temperatures, thus making this ecosystem particularly resilient to climate changes. In the second part, we present remote sensing-based analyses that investigate changes of vegetation health and function over the last six years, which were affected by both biotic (pest invasion) and abiotic (more frequent and intense droughts) factors.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Modelling PM10 removal in three Italian coastal Metropolitan Cities along a latitudinal gradient - L. Nardella; A. Sebastiani; M. Stafoggia; P.P. Franzese; F. Manes (Ecological Modelling, 2023)

More nature in the city - G Capotorti; S Bonacquisti; L Abis; I Aloisi; F Attorre; G Bacaro; G Balletto; E Banfi; E Barni; F Bartoli; E Bazzato; M Beccaccioli; et al. (Plant Biosystems, 2020)

Genetic polymorphism of APOB is associated with diabetes mellitus in sickle cell disease - Xu Zhang; Wei Zhang; Santosh L. Saraf; Mehdi Nouraie; Jin Han; Michel Gowhari; Johara Hassan; Galina Miasnikova; Adelina Sergueeva; Sergei Nekhai; Rick Kittles; Roberto F. Machado; et al. (Human Genetics, 2015)

Development and characterization of SSR markers for pomegranate (Punica granatum L.) using an enriched library - N. Hasnaoui; A. Buonamici; F. Sebastiani; M. Mars; M. Trifi; G. G. Vendramin (Conservation Genetics Resources, 2010)

Is Cupressus sempervirens native in Italy? An answer from genetic and palaeobotanical data - F. BAGNOLI; G. G. VENDRAMIN; A. BUONAMICI; A. G. DOULIS; S. C. GONZÁLEZ‐MARTÍNEZ; N. LA PORTA; D. MAGRI; P. RADDI; F. SEBASTIANI; S. FINESCHI (Molecular Ecology, 2009)
This study represents the first large‐scale analysis using nuclear molecular markers to assess genetic diversity and structure of Cupressus sempervirens L.. Genetic and fossil data were combined to infer the possible role of human activity and evolutionary history in shaping the diversity of cypress populations. We analysed 30 populations with six polymorphic nuclear microsatellite markers. Dramatic reductions in heterozygosity and allelic richness were observed from east to west across the species range. Structure analysis assigned individuals to two main groups separating central Mediterranean and eastern populations. The two main groups could be further divided into five subgroups which showed the following geographical distributions: Turkey with the Greek islands Rhodes and Samos, Greece (Crete), Southern Italy, Northern Italy, Tunisia with Central Italy. This pattern of genetic structure is also supported by samova and Barrier analyses. Palaeobotanical data indicated that Cupressus was present in Italy in the Pliocene, Pleistocene and Holocene. Furthermore, our molecular survey showed that Italian cypress populations experienced bottlenecks that resulted in reduced genetic diversity and allelic richness and greater genetic differentiation. Recent colonization or introduction may also have influenced levels of diversity detected in the Italian populations, as most individuals found in this range today have multilocus genotypes that are also present in the eastern range of the species. The data reveal a new interpretation of the history of cypress distribution characterized by ancient eastern populations (Turkey and Greek islands) and a mosaic of recently introduced trees and remnants of ancient, depauperate populations in the central Mediterranean range.

Physiological and productive responses of Olea europaea L. cultivars Frantoio and Leccino to a regulated deficit irrigation regime - R. D'andria; A. Lavini; G. Morelli; L. Sebastiani; R. Tognetti (Plant Biosystems, 2009)

In vitro olive ( Olea europaea L.) cvs Frantoio and Moraiolo microshoot tolerance to NaCl - T. Bracci; A. Minnocci; L. Sebastiani (Plant Biosystems, 2008)

Variation in mesophyll anatomy and photosynthetic capacity during leaf development in a deciduous mesophyte fruit tree (Prunus persica) and an evergreen sclerophyllous Mediterranean shrub (Olea europaea) - S. Marchi; R. Tognetti; A. Minnocci; M. Borghi; L. Sebastiani (Trees, 2008)

Deficit irrigation and fertigation practices in olive growing: Convergences and divergences in two case studies - R. Tognetti; A. Morales-Sillero; R. D'Andria; J. E. Fernández; A. Lavini; L. Sebastiani; A. Troncoso (Plant Biosystems, 2008)

The distribution of Quercus suber chloroplast haplotypes matches the palaeogeographical history of the western Mediterranean - D. MAGRI; S. FINESCHI; R. BELLAROSA; A. BUONAMICI; F. SEBASTIANI; B. SCHIRONE; M. C. SIMEONE; G. G. VENDRAMIN (Molecular Ecology, 2007)
Combining molecular analyses with geological and palaeontological data may reveal timing and modes for the divergence of lineages within species. The Mediterranean Basin is particularly appropriate for this kind of multidisciplinary studies, because of its complex geological history and biological diversity. Here, we investigated chloroplast DNA of Quercus suber populations in order to detect possible relationships between their geographical distribution and the palaeogeographical history of the western Mediterranean domain. We analysed 110 cork oak populations, covering the whole distribution range of the species, by 14 chloroplast microsatellite markers, among which eight displayed variation among populations. We identified five haplotypes whose distribution is clearly geographically structured. Results demonstrated that cork oak populations have undergone a genetic drift geographically consistent with the Oligocene and Miocene break‐up events of the European–Iberian continental margin and suggested that they have persisted in a number of separate microplates, currently found in Tunisia, Sardinia, Corsica, and Provence, without detectable chloroplast DNA modifications for a time span of over 15 million years. A similar distribution pattern of mitochondrial DNA of Pinus pinaster supports the hypothesis of such long‐term persistence, in spite of Quaternary climate oscillations and of isolation due to insularity, and suggests that part of the modern geographical structure of Mediterranean populations may be traced back to the Tertiary history of taxa.

Chromosome 17p12-q11 harbors susceptibility loci for systemic lupus erythematosus - CeciliaM. Johansson; Renata Zunec; MercedesA. Garca; HugoR. Scherbarth; GuillermoA. Tate; Sergio Paira; SandraM. Navarro; CarlosE. Perandones; Susana Gamron; Alejandro Alvarellos; CesarE. Graf; Jorge Manni; et al. (Human Genetics, 2004)

Molecular differentiation of the Old World Culicoides imicola species complex (Diptera, Ceratopogonidae), inferred using random amplified polymorphic DNA markers - F. Sebastiani; R. Meiswinkel; L. M. Gomulski; C. R. Guglielmino; P. S. Mellor; A. R. Malacrida; G. Gasperi (Molecular Ecology, 2001)
Samples of seven of the 10 morphological species of midges of the Culicoides imicola complex were considered. The importance of this species complex is connected to its vectorial capacity for African horse sickness virus (AHSV) and bluetongue virus (BTV). Consequently, the risk of transmission may vary dramatically, depending upon the particular cryptic species present in a given area. The species complex is confined to the Old World and our samples were collected in Southern Africa, Madagascar and the Ivory Coast. Genomic DNA of 350 randomly sampled individual midges from 19 populations was amplified using four 20‐mer primers by the random amplified polymorphic DNA (RAPD) technique. One hundred and ninety‐six interpretable polymorphic bands were obtained. Species‐specific RAPD profiles were defined and for five species diagnostic RAPD fragments were identified. A high degree of polymorphism was detected in the species complex, most of which was observed within populations (from 64 to 76%). Principal coordinate analysis (PCO) and cluster analysis provided an estimate of the degree of variation between and within populations and species. There was substantial concordance between the taxonomies derived from morphological and molecular data. The amount and the different distributions of genetic (RAPD) variation among the taxa can be associated to their life histories, i.e. the abundance and distribution of the larval breeding sites and their seasonality.

Intron size polymorphism of the Adh 1 gene parallels the worldwide colonization history of the Mediterranean fruit fly, Ceratitis capitata - L. M. GOMULSKI; K. BOURTZIS; S. BROGNA; P. A. MORANDI; C. BONVICINI; F. SEBASTIANI; C. TORTI; C. R. GUGLIELMINO; C. SAVAKIS; G. GASPERI; A. R. MALACRIDA (Molecular Ecology, 1998)
The exon‐primed intron‐crossing (EPIC) PCR technique was used to analyse the size variation at the first intron of the Ceratitis capitata Adh 1 gene. A total of 27 samples from 16 natural populations was analysed from five geographical regions in the species range: Africa, Mediterranean Basin, Latin America, Hawaii and Australia. The Adh 1 first intron varies extensively in length with at least 18 size variants ranging from 1400 bp to 3450 bp. These variants can be grouped into four distinct size categories: short, medium, long and very long. The majority of these variants are present only in the African populations. Only a subset of the ancestral variants appear to have succeeded in migrating from Africa during the medfly colonization process. The medfly population structure inferred from the intron size polymorphism is congruent with that observed from the analysis of allozyme variation. The geographical dispersal of the medfly from its source area is associated with a gradual and great reduction in intron variability which parallels the trend of decreasing variability evaluated at 26 biochemical loci. The intron phylogenetic tree is in agreement with allozyme data in portraying the dynamic population history of the medfly. Stochastic evolutionary forces such as drift, bottleneck effects and migration seem to have played the major roles in the dispersion pattern of Adh 1 intron variation during the colonization of the medfly.